2018
DOI: 10.30831/akukeg.410279
|View full text |Cite
|
Sign up to set email alerts
|

Bilişim Teknolojileri Özyeterliği Cinsiyet Açığı: Ortaokul Matematik Öğretmenlerine Yönelik Bir İnceleme

Abstract: In the research, it is aimed at to examine the self-efficacy levels of information technology of secondary school mathematics teachers according to gender. The study also finds out whether the self-efficacy levels of male and female teachers differ according to professional experience. In the study, a causal comparative research design one of the quantitative research methods is used. The research population is composed of secondary school mathematics teachers taught in Çanakkale. Based on the principle of vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In similar studies, significant differences in favour of male prospective teachers have been found in the ICT attitudes, virtual communication, computer hardware and software usage sub-dimensions (Bakırcı and Günbatar, 2017), technology integration selfefficacy, technology knowledge dimension (Şimşek and Yazar, 2018), attitudes towards technology (Şen and Timur, 2018), information security knowledge levels (Gökmen and Akgün, 2014) views on information technology teacher competencies as well as technological practices and support competencies (Dursun and Saracaloğlu, 2017) of the prospective teachers. Similarly, it has been concluded in the studies conducted with teachers that there was a significant difference in teachers' self-efficacy perceptions of technology (Kartal, Temelli and Şahin, 2018), their technology acceptance levels (Sırakaya, 2019) and their educational technologies usage levels (Çelik and Demirtaş, 2019) in favour of male teachers. Moreover, in the study conducted with prospective teachers on digital literacy, which is defined as accessing information and conducting research using digital technologies and integrated with ICT, it has been determined that male prospective teachers felt more competent in digital literacy than female prospective teachers (Öztürk and Budak, 2019).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 86%
“…In similar studies, significant differences in favour of male prospective teachers have been found in the ICT attitudes, virtual communication, computer hardware and software usage sub-dimensions (Bakırcı and Günbatar, 2017), technology integration selfefficacy, technology knowledge dimension (Şimşek and Yazar, 2018), attitudes towards technology (Şen and Timur, 2018), information security knowledge levels (Gökmen and Akgün, 2014) views on information technology teacher competencies as well as technological practices and support competencies (Dursun and Saracaloğlu, 2017) of the prospective teachers. Similarly, it has been concluded in the studies conducted with teachers that there was a significant difference in teachers' self-efficacy perceptions of technology (Kartal, Temelli and Şahin, 2018), their technology acceptance levels (Sırakaya, 2019) and their educational technologies usage levels (Çelik and Demirtaş, 2019) in favour of male teachers. Moreover, in the study conducted with prospective teachers on digital literacy, which is defined as accessing information and conducting research using digital technologies and integrated with ICT, it has been determined that male prospective teachers felt more competent in digital literacy than female prospective teachers (Öztürk and Budak, 2019).…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 86%